Perineal Injury with Vaginal Delivery; What are the Risks - Amber Abbasi, Saira Talpur, Sehrish Khan, Shazia Awan, Geeta Bai, Rashida Akbar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To observe the severity of the perineal trauma and its risk factors among women who developed perineal tears during vaginal delivery. Material and methods: This descriptive cross-sectional study was conducted at the Obstetrics and genecology department of LUMHS, Hyderabad, Pakistan, from September 2016 to August 2017. All the women who developed perineal trauma during vaginal delivers, age 18–40 years, singleton pregnancy, both primiparous and multiparous were included. After delivery, patients who had developed perineal tears were assessed for its severity and risk factors. Perineal tears were categorized as per severity in four categories All the data were collected via study proforma and for the analysis of data, the 26 versions of SPSS were employed. Results: A total of 100 cases were studied in the study and most of the patients 45.0% were in the age group of 15–25 years. The average gestational age was 38.2+4.1 weeks. Primiparous cases were 65.0%. Un-booked women were 65.0%. 30.0% underwent mediolateral episiotomy and 19.0% with a midline cut extension. Most of the women 41.0% were delivered by NVD, followed by 26.0% by assist vaginal delivery and while 33.0% women underwent instrumental vaginal delivery. According to the birth weight the 40.0% babies weighing more than 2.5 kg. 40.0% females had a first-degree perineal tear, followed by 32.0 percent had a second-degree tear, 19.0 percent had third-degree tear, and 10.0 percent had a fourth-degree perineal tear. Conclusion: Perineal trauma of 3rd and 4th degree were observed to be 19% and 10%, respectively. Maternal age less than 25 years, primiparity, un-booked status, use of the oxytocin, previous history of the vaginal surgeries and fetal weight >2.5 kg were observed the risk factors of the perineal tear.